Pronounced Phenotypic Changes in Transgenic Tobacco Plants Overexpressing Sucrose Synthase May Reveal a Novel Sugar Signaling Pathway - Nguyen, Quynh Anh; Luan, Sheng; Wi, Seung G.; Bae, Hanhong; Lee, Dae-Seok; Bae, Hyeun-Jong (Frontiers in Plant Science, 2016)
Soluble sugars not only serve as nutrients, but also act as signals for plant growth and development, but how sugar signals are perceived and translated into physiological responses in plants remains unclear. We manipulated sugar levels in transgenic plants by overexpressing sucrose synthase (SuSy), which is a key enzyme believed to have reversible sucrose synthesis and sucrose degradation functions. The ectopically expressed SuSy protein exhibited sucrose-degrading activity, which may change the flux of sucrose demand from photosynthetic to non-photosynthetic cells, and trigger an unknown sucrose signaling pathway that lead to increased sucrose content in the transgenic plants. An experiment on the transition from heterotrophic to autotrophic growth demonstrated the existence of a novel sucrose signaling pathway, which stimulated photosynthesis, and enhanced photosynthetic synthesis of sucrose, which was the direct cause or the sucrose increase. In addition, a light/dark time treatment experiment, using different day length ranges for photosynthesis/respiration showed the carbohydrate pattern within a 24-hour day and consolidated the role of sucrose signaling pathway as a way to maintain sucrose demand, and indicated the relationships between increased sucrose and upregulation of genes controlling development of the shoot apical meristem (SAM). As a result, transgenic plants featured a higher biomass and a shorter time required to switch to reproduction compared to those of control plants, indicating altered phylotaxis and more rapid advancement of developmental stages in the transgenic plants.